Analisis Pengaruh Node Density pada Vehicular Ad Hoc Network (VANET) dengan menggunakan Protokol Routing Dynamic Source Routing (DSR) di Model Jalan Perkotaan - Rexy Marten; Dany Primanita Kartikasari; Fariz Andri Bakhtiar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
VANET is a wireless network which using vehicle as a moving node for exchange information and provide comfort and security for vehicle user. Characteristics of VANET are high mobility and different number of vehicle. Number of vehicle in urban area is affected by activity on the area at certain hour such as rush hour in the morning and evening, this caused number of vehicle varies. Previous research stated that DSR is a reactive routing protocol that able to work in VANET and produces good performances based on overhead, packet delivery ratio, and normalized routing load parameter. This study presents an analysis of the effect of node density in VANET network using DSR in urban model area as the simulation. Testing is based on changes in the number of nodes using 30, 60, 90, 120, 150 and 300 nodes with testing parameters end to end delay packet and delivery ratio, also using coefficient determination, F test, and T test for validity testing. The result showed that node density impacted VANET performance when using linier regression for validity testing. The performance of VANET by using DSR produces the best end to end delay in 30 nodes with 3057.79ms, and the worst in 300 nodes with 25432.9ms, while in packet delivery ratio parameter produces the packet successfully sent in 300 nodes with 92.79%, and the least in 30 nodes with 76.88%.